PENGARUH SUKUK TERHADAP NILAI PERUSAHAAN DAN IMPLIKASINYA TERHADAP KESEJAHTERAAN PEMEGANG SAHAM - Teguh Rimbawan; Negina Kencono Putri; Siti Maghfiroh (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2019)
The purpose of this study is to prove empirically that Sukuk has a positive effect on Corporate Value, and to prove empirical that the Company Value is a factor that mediates the correlation between Sukuk with Shareholder Welfare. The population in this study is a company that issued sukuk and listed on BEI. The method of determining the sample is purposive sampling method. It is obtained 12 sample companies with total observation as much as 42. Based on the results of research and data analysis using Product of Coefficient / Sobel test method (Sobel, 1982), shows that Sukuk has no positive effect on Corporate Value, and Corporate Value is not a factor mediating relationship between Sukuk Financing with Shareholder Welfare. The theoretical implications of the results of this study do not support alternative hypotheses. This can be attributed to the fact that the sukuk financing owned by the sample companies is too small, averaging 2.3% of the total assets, so that the effect of the changes between the variables tested becomes insignificant. The small proportion of sukuk corporations due to sukuk has not been seen as a beneficial effect either in the eyes of companies, creditors, and investors. Keywords: Sukuk, Firm Value, Shares Holders Welfare, Product of coefficien, Sobel test.